Penning-type H⁻ ion source with metal hydride cathode in pulsating regime - Sereda, I.; Hrechko, Ya.; Azarenkov, N. (Problems of Atomic Science and Technology, 2023)
The features of H⁻ ion emission from gas-feed-free Penning-type ion source with metal hydride cathode have been studied in pulsating regime. The metal hydride cathode provided local injection of hydrogen in activated state and impacts on Penning discharge ability to emit H⁻ ions in the longitudinal direction. For stimulation of pre-excited hydrogen desorption from metal hydride the voltage pulse (4.5 kV, τ ≈ 15 μs) was performed against the background constant voltage of 6 kV on the anode of the discharge. The H⁻ ion current of about 0.2 mA was obtained. Досліджено особливості емісії іонів H⁻ джерела іонів пеннінгівського типу з металогідридним катодом у пульсуючому режимі. Металогідридний катод забезпечував локальну інжекцію водню в активованому стані та впливав на здатність пеннінгівського розряду емітувати іони H⁻ у поздовжньому напрямку. Для стимуляції десорбції попередньо збудженого водню з гідриду металу до анода розряду підводили імпульс напруги (4,5 кВ, τ ≈ 15 мкс) на фоні постійної напруги 6 кВ. Отримано струм іонів H⁻ близько 0,2 мА.